Olah Tubuh sebagai Stimulus untuk Meningkatkan Kemampuan Melakukan Gerak Tari Anak pada Ekstrakurikuler di SDN Dukuh 09 Pagi Jakarta Timur - Juwita, Mony (Program Studi Pendidikan Tari FBS UNJ, 2020)
The ability to move dance is part of dance activities that must be possessed by students in the experience of the dance learning process. However, there are still many students whose ability to dance is still lacking. Exercise is an effort that can be done to improve the ability to move dance. This study aims to improve the dance movement skills of students through the application of body exercises in extracurricular classes for students at one of the SDN East Jakarta. The method used in this research is the method of action which is carried out in two cycles which include planning, action, observing, and reflecting. Data collection techniques in the form of interviews, tests, observation and documentation. Qualitative data analysis techniques used Miles & Huberman with the stages of data reduction, data presentation, and conclusion, while quantitative analysis used descriptive statistics. The results showed that body exercise could improve the students' ability to dance based on wiraga elements with an average value of 3.87 and a percentage of 98.5%, elements of wirama with an average value of 3.1 and a percentage of 62%, and elements of wirasa with a value average 3.7 and a percentage of 74%. This research can be continued with the implementation of other dance activities to improve the students' dance abilities, and it can also be done using other research methods.